Material flow cost accounting (MFCA)-based approach for prioritisation of waste recovery - Wan, Yoke Kin (Animo Repository, 2015)
© 2015 Elsevier Ltd. Waste recovery has become one of the most important strategies to reduce environmental issues and improve economic performance in industry. Thus, different systematic approaches have been developed for waste recovery. However, most of the developed waste recovery approaches do not account for the hidden cost incurred from various processing steps as a criterion for prioritisation of waste recovery. This aspect can be determined by the concept of material flow cost accounting (MFCA). Hence, in this work, a novel MFCA-based approach is developed for prioritisation of waste recovery with consideration of hidden costs embedded in process streams. Two case studies are solved to illustrate the developed approach. It can be seen that hidden unit cost (HUC), carry-forward cost (CFC), amount and quality of discharged waste are important factors that significantly affect the prioritisation results. The developed approach then balances the trade-off among these factors to determine the minimum total hidden cost (THC) of discharged waste, and thus improve the economic and environmental performances of an industrial process.